2020
DOI: 10.1109/jphot.2020.2992135
|View full text |Cite
|
Sign up to set email alerts
|

EWT-ASG: Empirical Wavelet Transform With Adaptive Savitzky–Golay Filtering for TDLAS

Abstract: Inspired by the empirical mode decomposition (EMD)-enhanced gas detection work, this paper develops a further improved signal reconstruction method (namely EWT-ASG) for the demodulated harmonics of tunable diode laser absorption spectroscopy (TDLAS), which is mainly based on empirical wavelet transform (EWT) and Savitzky-Golay (S-G) filtering. First, the imported EWT performs better on the decomposition precision as it successfully bypasses the mode aliasing problem of EMD resulting by the lack of mathematical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…Since then, a series of studies, such as ensemble empirical mode decomposition (EEMD) 17 and complete ensemble empirical mode decomposition with adaptive noise (CEEMDAN) 18 , were proposed, but none of them could fundamentally make up for the lack of mathematical basis and theoretical support. He et al proved that empirical wavelet transform (EWT) outdoes EMD for the multi-resolution characteristics and flexibility to signals 19 , and the wavelet decomposition applied in an industrial scene 20 has been confirmed superior to deal with timevarying noises. Previously, Song et al proposed a noise-robust self-adaptive support vector machine (NSSVM), especially for the case of fast and slow time-varying noise interleaving 21 .…”
Section: Introductionmentioning
confidence: 99%
“…Since then, a series of studies, such as ensemble empirical mode decomposition (EEMD) 17 and complete ensemble empirical mode decomposition with adaptive noise (CEEMDAN) 18 , were proposed, but none of them could fundamentally make up for the lack of mathematical basis and theoretical support. He et al proved that empirical wavelet transform (EWT) outdoes EMD for the multi-resolution characteristics and flexibility to signals 19 , and the wavelet decomposition applied in an industrial scene 20 has been confirmed superior to deal with timevarying noises. Previously, Song et al proposed a noise-robust self-adaptive support vector machine (NSSVM), especially for the case of fast and slow time-varying noise interleaving 21 .…”
Section: Introductionmentioning
confidence: 99%
“…Feng Shiling et al [4] processed direct absorption spectra and second harmonic signals with different concentrations using wavelet transform noise reduction techniques and obtained a signal-to-noise ratio increase of more than 500 times, which proved the value of using wavelet transform in this field. Zou Debao et al [5] processed the TDLAS ammonia absorption signal using a variety of different filtering methods, and the results showed that the wavelet transform plus arithmetic averaging method was able to increase the signal-to-noise ratio by a factor of 14. Zhang Shuai et al digitally filtered the concentration signal by modified weighted moving average filtering, which improved the signal-to-noise ratio and the detection sensitivity of the system, and was applied to the real-time hydrogen sulfide detection in a natural gas processing plant.…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, because EWT is not decomposed in an iterative way, the decomposition speed is very fast. Due to the above advantages, EWT has been widely used in the identification of the fault information of rolling bearings [ 20 , 21 ] and fan bearings [ 22 ]. In this paper, EWT is introduced into the processing of the foundation vibration signals and is used to perform the multi-scale decomposition of foundation vibration signals.…”
Section: Introductionmentioning
confidence: 99%